Exploration of Application of Unmanned Aerial Vehicle Remote Sensing Monitoring Technology in Reservoir Management—Taking a Reservoir in South China as an Example - SUN Wen; SUN Bo (Renmin Zhujiang)
In order to improve the technological level and efficiency of water conservancy project supervision,a drinking water reservoir management department in South China took the lead in building a set of intelligent patrol systems for unmanned aerial vehicles (UAVs).The system included UAVs,UAV automated airports,meteorological monitoring devices,and UAV dispatch and control platforms,and it integrated technologies such as UAV autonomous driving,remote-sensing monitoring,geospatial perception,and artificial intelligence,achieving intelligent flight operations of UAVs in a round-the-clock,fully automatic,and highly frequent manner.It changed traditional routine inspection methods for reservoir security,environment,and land space,greatly improved working efficiency and regulatory effectiveness,and reduced the occurrence of safety incidents around the reservoir,which provided a certain reference value for its application and promotion in the daily management of water conservancy projects.However,the technical issues such as battery life,communication interference,and intelligent perception in the application of UAVs in the industry,as well as the lack of UAV hardware quality and flight standards caused by incomplete industry regulation,collectively limited the orderly development of the industry,and it must be taken seriously by industry-related regulatory authorities.